A new discrete GaN-based dv/dt control circuit for megahertz frequency power converters - Bright K. Banzie; John K. Annan; Francis B. Effah (e-Prime: Advances in Electrical Engineering, Electronics and Energy)
In this paper, we present a novel GaN-based discrete current mirror active gate driver (AGD) for closed-loop dv/dt control, designed specifically for megahertz (MHz) frequency power converters employing power devices with low reverse transfer capacitance (CRSS) values. The proposed AGD circuit, implemented using four N-channel GaN FETs, addresses the limitations of existing dv/dt control methods by providing a high-bandwidth, high-gain solution without the complexity of integrated circuits or reliance on conventional complementary current mirror configuration. Experimental validation in a 10 MHz, 24 V buck converter demonstrates a significant reduction in the turn-on dv/dt of the low-side switch from -15 V/ns to -11 V/ns, achieved with a small 0.1 pF sensor capacitor. This reduction was realised while maintaining sub-nanosecond-level response time and ensuring effective dv/dt regulation during the turn-on switching transient. Simulation results, verified through PSpice models, confirm the AGD's ability to generate feedback currents several orders of magnitude higher using the small sensor capacitor, thereby reducing gate current and enhancing system stability. The circuit design also benefits from using GaN technology, enabling higher switching frequencies and improved power conversion efficiency. This work offers a promising solution for discrete dv/dt control in MHz frequency applications, providing a foundation for future advancements in GaN-based AGD systems.